Bizzy Bear : pirate adventure - Davies, Benji (Somerville, Mass. : Nosy Crow, 2013)
Bizzy Bear and his animal friends set sail on a pirate ship in search of a treasure chest filled with golden coins.
Cover title.
Keywords: Toy and movable books -- Specimens; Board books; Bears -- Fiction; Pirates -- Fiction; Stories in rhyme; Slide-and-peek books; Toy and movable books; Board books; Bears -- Fiction; Pirates -- Fiction; Toy and movable books; Board books for children; Stories in rhyme